Reconstruction of EMI Sources for PCBs Based on Adaptive Differential Evolution Algorithm - Ma, Xiao; Wang, Junjun; Hou, Chunbin; Wu, Qi (IEEE transactions on electromagnetic compatibility, 2025)
A phaseless reconstruction method of equivalent electromagnetic interference (EMI) sources for printed circuit boards (PCBs) based on the success-history based adaptive differential evolution algorithm with linear population size reduction(L-SHADE) is proposed. The equivalent sources are modeled by electric and magnetic dipoles placed over a planar surface on the PCB, and the magnitudes of magnetic fields are obtained through near-field (NF) scanning and used as reference data. To determine the initial range of dipole moment and the number of dipoles, a repeated iterative strategy combining the truncated singular-value decomposition (SVD) method is proposed and integrated into the optimization process. The effectiveness and accuracy of the proposed method are verified by comparing the full-wave simulation results with source reconstruction results for PCBs featuring various types of traces. Based on the simulation, an NF scanning experiment is conducted on an actual circuit to reconstruct EMI sources, further validating the feasibility of the proposed method.